PERBEDAAN PENGETAHUAN TENTANG BAHAYA MEROKOK REMAJA SMP N 3 BELANG SEBELUM DAN SESUDAH PENYULUHAN MENGGUNAKAN MEDIA VIDEO - Indah Raranda; Beatrix J. Podung; P. Pingkan (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2024)
Smoking in the community environment is often considered a trivial matter in society, even though smoking can have several effects in the community environment, especially in adolescence and in improving the health status of the community. The problem in this research is: Is there a difference between teenagers at SMP N 3 Belang regarding the dangers of smoking before and after counseling using video media? Research objective: to determine the difference in knowledge of teenagers at SMP N 3 Belang about the dangers of smoking before and after counseling using video media. Research Hypothesis: There is a difference in the knowledge of teenagers at SMP N 3 Belang about the dangers of smoking before and after counseling using video media. The type of research used is quasi-experimental or quasi-experimental research. The population in this study was taken from 45 students of SMP N 3 Belang. The research design uses: Randomized control groups pre-test and post-test design. Hypothesis testing uses the Wilcoxom matched pairs analysis technique with SPSS. The results of hypothesis analysis using the Wilcoxom test obtained a p value = 0.000 < 0.05 using a confidence level of 95%, thus the null hypothesis (H0) was rejected and the alternative hypothesis (Ha) was accepted. Research conclusion: There is a difference in the knowledge of teenagers at SMP N 3 Belang about the dangers of smoking before and after counseling using video media.